2021
DOI: 10.1080/09064702.2020.1869817
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and behavioural responses of Swedish domestic goats and their kids (Capra hircus) to 15 days of heat exposure

Abstract: Seven Swedish domestic goats (Capra hircus, 2-3 years) and their kids (37 ± 4 days) were subjected to indoor temperatures above 30°C during 15 days (periods H1-H4; periods without heat C1, C2) to study acclimation. Rectal temperature (RT) increased by 1.1°C during H1 to H3 (P < 0.001 vs. C1), but only by 0.6°C during H4 (P < 0.001 vs. C1; P < 0.024 vs. H1). Respiration rate (RR) increased less during H4 than during H1 (P < 0.001). Skin temperature increased during heat (P < 0.001), and skin evaporation (SE), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The longer time spent lying during the hot conditions might be an adaptive behavior to reduce additional heat production from body movements, and this corresponded to the decrease in change position frequency. The longer lying time during heat stress was also reported in goats [26,38,39] and sheep [40], but another study in goats [41] found that lying time was lowered during heat stress. In addition, Salama et al [26] reported that changing the position increased under heat stress, reflecting goats' uncomfortable behavior.…”
Section: Behavioral Responsesmentioning
confidence: 70%
“…The longer time spent lying during the hot conditions might be an adaptive behavior to reduce additional heat production from body movements, and this corresponded to the decrease in change position frequency. The longer lying time during heat stress was also reported in goats [26,38,39] and sheep [40], but another study in goats [41] found that lying time was lowered during heat stress. In addition, Salama et al [26] reported that changing the position increased under heat stress, reflecting goats' uncomfortable behavior.…”
Section: Behavioral Responsesmentioning
confidence: 70%